Natalidade em Salvador, Bahia (Brasil) Childbirth in Salvador, BA, Brazil - Maura Maria Guimarães de Almeida (Universidade de São Paulo, 1981)
Foi estudada a natalidade em Salvador, Bahia (Brasil) através de uma amostra probabilística de 2.893 domicílios, calculando-se uma taxa de fertilidade de 96,87 por mil mulheres em idade fértil e uma taxa de natalidade de 32,97. Verificou-se associação entre o número de filhos e a renda, utilizando-se como indicadores da renda a zona de residência, classificação do bairro e a ocupação da mãe. O número de filhos está também associado a escolaridade. In a random sampling of 2893 households in Salvador, BA, Brazil, the birth rate was focused on, the fertility rate was found to be 96.87 per 1000 women of child-bearing age, and the birth rate was 32.97. For this survey, residential area and mother's occupation were used as income indicators which pointed out two inverse relationships: 1) an inverse association between the number of children and income was statistically significant; 2) the same was true in the mother's educational level versus number of children.